Não entendi ,alguém pode me ajudar?!
![x { }^{2} - 6x - 91 = 0 x { }^{2} - 6x - 91 = 0](https://tex.z-dn.net/?f=x++%7B+%7D%5E%7B2%7D++-+6x+-+91+%3D+0)
Soluções para a tarefa
Respondido por
1
resolução!
∆ = ( - 6 )^2 - 4 * 1 * ( - 91 )
∆ = 36 + 364
∆ = 400
∆ = √ 400
∆ = 20
X ' = 6 + 20 / 2
X ' = 26 / 2
X ' = 13
X " = 6 - 20 / 2
X " = - 14 / 2
X " = - 7
S = { - 7 , 13 }
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Matemática,
1 ano atrás
Informática,
1 ano atrás